Synthesis and evaluation of delayed anti-high temperature gel plugging agent - Bai, Yang; Wu, Lingfeng; Luo, Pingya; Li, Daoxiong (Frontiers in Energy Research, 2022)
The malignant leakage of complex formations seriously restricts the drilling time, and has become a major drilling technical problem to be solved urgently at this stage. In particular, the malignant leakage of large fractures and fractured formations is difficult to construct and the success rate of plugging is low. In this paper, according to the above formation conditions, by analyzing the leakage mechanism of the malignant leakage formation, the method of plugging the large fractures and broken fractured formations is summarized. Using gelatin and acrylamide (AM) as the main raw materials, using 2-methacrylamide as the initiator, and using its multi-point initiation characteristics, the cross-linking agent realizes high-strength bonding between the covalent bonds of organic polymers, The invention is a gel plugging agent with controllable gel formation time, stable gel formation and good gel breaking performance, and is suitable for crushing leakage under high temperature and high pressure conditions in wells. The effect of temperature on gel formation, gel rheological properties under high temperature and high pressure, gel initiation pressure and gel breakability tests were evaluated under laboratory conditions. The experimental results show that the gelation time of the gel in the experimental slurry is 60 minutes; when the concentration of the gel in the experimental slurry exceeds 2%, its rheological properties change abruptly; under certain conditions, the starting pressure of the gel can reach up to 6.5MPa; Under the condition of 150℃, the gel breaking rate was over 98% after 24 hours. Various experiments show that the performance of the gel meets the requirements for plugging of malignant leakage formations, and the effect is good.